The Influence of Regional Original Income (PAD) and General Allocation Fund (DAU) on Capital Expenditure in the Jambi Provincial Government 2015–2025 - Selia Meilantika; Sri Rahayu; Rico Wijaya (International Journal of Business and Quality Research, 2026)
This study aims to analyze the influence of Regional Original Revenue (PAD) and General Allocation Fund (DAU) on Capital Expenditure in the Jambi Provincial Government for the 2015-2025 period. The study uses a quantitative method with secondary data obtained from the Jambi Provincial Government Budget Realization Report published by the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. The research sample consists of 11 observations derived from time series data for the 2015-2025 period. Data analysis techniques used include descriptive statistics, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, coefficient of determination (R²) tests, F tests, and t tests with the help of the Statistical Package for Social Sciences (SPSS) program. The results of the study indicate that Regional Original Income (PAD) does not significantly influence Capital Expenditure with a significance value of 0.520. The General Allocation Fund (DAU) also does not significantly influence Capital Expenditure with a significance value of 0.455. Simultaneously, PAD and DAU do not significantly influence Capital Expenditure with a significance value of 0.708 in the F test. The coefficient of determination (R²) of 0.083 indicates that PAD and DAU are only able to explain variations in Capital Expenditure by 8.3%, while the remaining 91.7% is explained by other factors outside the research model. The results of this study indicate that the Capital Expenditure of the Jambi Provincial Government during the research period is not significantly influenced by PAD and DAU, but is likely more influenced by other factors such as the Special Allocation Fund (DAK), Revenue Sharing Fund (DBH), Budget Financing Surplus (SiLPA), and regional budgeting policies. Keywords: Regional Original Income, General Allocation Fund, Capital Expenditure, Regional Finance, Jambi Provincial Government.